Pengaruh Tingkat Pendidikan Dan Kesehatan Terhadap Kemiskinan (Studi Kasus Provinsi Aceh) - Novita Annisa; Khairil Anwar (Jurnal Ekonomi Regional Unimal, 2021)
This study aims to determine the effect of education level and health on poverty in Aceh. This study uses secondary data obtained from the Aceh Central Statistics Agency in 2007-2019. The data analysis method used is multiple linear regression analysis. The results partially show that education level and health has a negative and significant effect on poverty in Aceh. Simultaneously, education level and health have a positive and significant effect on poverty in Aceh.